Identification of gene co-expression networks and key genes regulating flavonoid accumulation in apple (Malus × domestica) fruit skin. (March 2021) - Ding, Tiyu; Zhang, Ruiping; Zhang, Hengtao; Zhou, Zhe; Liu, Chonghuai; Wu, Mengmeng; Wang, Huan; Dong, Haiqing; Liu, Jihong; Yao, Jia-Long; Yan, Zhenli
Highlights: MdMYB28 is a R2R3-type MYB family gene, as a repressor of anthocyanin accumulation in apple fruit skin. MdMYB28 expression level was negatively correlated with anthocyanin content in apple fruit skin. Overexpression of MdMYB28 reduced the anthocyanin biosynthesis in tobacco flower petals. Abstract: Anthocyanin provides a red color for apple and health benefit for human. To better understand the molecular mechanisms of regulating apple color formation, we analyzed 27 transcriptomes of fruit skin from three cultivars 'Huashuo' (red-skinned), 'Hongcuibao' (red-skinned), and 'Golden Delicious' (yellow-skinned) at 0, 2, and 6 days after bag removal. Using pairwise comparisons and weighted gene co-expression network analyses (WGCNA), we constructed 17 co-expression modules. Among them, a specific module was negatively correlated to anthocyanin accumulation. The genes in the module are enriched in flavonoid biosynthesis pathways. These pathway genes were used to construct gene co-expression network of anthocyanin accumulation. Finally, a R2R3-MYB repressor designated MdMYB28 was identified as a key hub gene in the anthocyanin metabolism network. During the anthocyanin accumulation of apple fruit skin reaching a peak, MdMYB28 expression level was negatively correlated with the anthocyanin content. MdMYB28 was shown to directly bind to the promoter of MdMYB10 in yeast one-hybrid analyses. Over-expression of MdMYB28 decreased the anthocyanin biosynthesis in tobacco flower petals, suggesting that MdMYB28 acts as a negatively regulator of anthocyanin biosynthesis.